Adapting TAM to Understand Video Conferencing Apps Adoption for Learning Islamic Knowledge - Nindita Erwanti (Department of Informatics Engineering, 2022)
Seeking knowledge is obligatory for Muslims. Video conferencing apps help Muslims for learning Islamic knowledge. This study attempted to comprehend factors influencing intention to use video conferencing applications for learning Islamic knowledge by modifying Technology Acceptance Model (TAM). The data was gathered through a questionnaire from 85 respondents. Partial Least Square-Structural Equation Modeling (PLS-SEM) was used to evaluate the proposed model. The findings show that perceived usefulness, perceived ease of use, and religiosity all have a significant influence on behavioral intention to use video conferencing apps. Furthermore, religiosity significantly influences perceived usefulness. Facilitating condition also significantly influences perceived usefulness and perceived ease of use.